Mapping of Landslide Hazard Distribution in Alo Watershed Gorontalo Regency - Risman Jaya; Ahmad Syamsu Rijal (Jambura Geoscience Review, 2020)
Landslide occurrence can be influenced by physical factors and human activities. Thus, research related to the provision of information about landslide distribution in Alo watershed is needed as a basis in enhancing community preparedness in dealing with disasters. The method used in this study is the scoring method based on the Minister of Public Works Regulation No.22 / PRT / M / 2017 which is processed through a geographical information system through the overlay of all physical parameters. The result shows that the Alo watershed area is divided into three vulnerability categories. "Low" category covers 7171.8 ha, "medium" category covers 12008.7 ha, and "high" category covers 5039.5 ha out of 24.221 ha the total area of Alo watershed. Information provided in this research is expected to be able to help the local government in making policies in managing the Alo watershed area and enhancing the understanding of the local community in Alo watershed in dealing with disasters.